Quantum dynamics of nonlinear excitations in the Ablowitz-Ladik model - Umarov, Bakhram (2013)
The investigation of the dynamics of nonlinear systems becomes a hot topic in modern science and engineering. One of the most challenging problem is the quantum evolution of nonlinear excitations which has many applications in condensed matter physics, quantum optics, quantum information and other areas of physics. Many different methods were suggested and implemented in this direction, both analytical and numerical. Among the most fruitful approaches are the so called phase space representations of quantum dynamics. In this method the evolution equation for quantum density operator is converted to the partial differential equation for some classical quasi-distribution function, which in some cases can be reduced to the system of ordinary stochastic differential equations. In this paper we are presenting the results of the investigation of quantum Ablowitz-Ladik model by the phase space representation methods. The classical Ablowitz-Ladik equation is the integrable discretization of Nonlinear Schrodinger Equation. The quantum dynamics of solitons and their interaction will be discussed, based on the results of the numerical simulation. The possibility of the quantum entanglement and squeezing in quantum Ablowitz-Ladik model will be investigated.